Intricacy of Plea Bargain in Uganda Criminal Justice - Leslie Stephanas Dogo (Uganda Christian University, 2025)
Through the aid of desk review, this study examines the extent to which plea bargain has facilitated in the promotion, protection and enforcement of justice in Uganda’s criminal justice system. The study highlights how plea bargain have been a tool in the alleviation of case backlogs in Uganda, protection of the rights of accused persons, reduction of prison congestion alongside improvement of inmates’ health condition, promotion of reconciliation rather than retribution and also put an end to unpredictable lengthy litigation. In evaluation of the nature of plea bargain, amid the several benefits which plea bargain inputs in to Uganda’s criminal justice system, statistics and studies have shown that plea bargain while addressing the shortcomings of the pre-existing procedure for criminal litigation, plea bargain has apposition new challenges which goes against both its core objectives and the principles of law which governs the administration of justice. All things considered, while understanding the positive roles of plea bargain programs in Uganda and how it tends to create new challenges, it is kin to acknowledge how all this affects the accused individual(s), the aggrieved party, and the society at large.
Dissertation